Communicative Leadership Strategy: Optimizing Inter-Division Interaction to Enhance Organizational Effectiveness - Sunarso, Budi (ADMAN: Journal of Contemporary Administration and Management, 2024)
In the era of globalization and rapid information technology development, organizational effectiveness becomes increasingly crucial for long-term success and competitiveness. This study aims to explore how communicative leadership strategies can be implemented to optimize inter-division interaction and enhance organizational effectiveness. This research uses a literature review method with a qualitative approach. The data collection process began with a search for scientific articles using the Google Scholar database, with publication dates ranging from 2001 to 2024. The results of the study indicate that open, honest, and two-way communication between leaders and team members can create a collaborative and productive work environment. Examples from companies like Google, hospitals in the United States, Toyota, and Stanford University demonstrate how communicative leadership can be successfully applied to improve coordination, innovation, and operational efficiency. This study concludes that organizations need to invest resources in training programs focused on developing interpersonal communication skills, conflict resolution, and teamwork. Leaders and employees should be trained to communicate effectively and overcome communication barriers.